TIL O`RGANISHNING INSON HAYOTIDAGI O`RNI - Xakimjonova Sevinch O`lmasboy Qizi, (TADQIQOTLAR, 2026)
Abstract This explores  the  importance  of language learning in human life focusing on mental  , article social, cultural, and professional dimensions. The research  is based on the author’s critical observations, comparative analysis, and personal findings  rather than  simple  literature  review.  The  relationship  between  language  and  thinking  is examined through the ideas of classical scholars and modern linguists. Furthermore, the  role  of  foreign  language  learning  in  the  era  of  globalization  and  its  impact  on personal development, flexible, and social integration are highlighted. The findings show  that  language  learning  plays  a  critical  role  in    cognitive    development  and professional advantage.